Performance enhancement and scaling control with gas bubbling in a direct contact membrane distillation - Chen, Guizi (2013)
This study incorporates gas bubbling into direct contact membrane distillation (DCMD) and examines its effect on the MD performance especially at elevated salt concentrations in the feed steam. Process optimization in the bubbling assisted DCMD process was carried out which involved varying operating conditions and module conﬁgurations. Also, observations were performed for the scaling status on the membrane surface with operating time in different modules to further understand the role of gas bubbling in affecting the behavior of crystal deposition when the salt concentration has reached super-saturation. Due to intensiﬁed local mixing and physical ﬂow disturbance in the liquid boundary layer on the feed side, a higher ﬂux enhancement could be achieved in a bubbling system with either a higher feed operating temperature, lower feed and permeate ﬂow velocities, inclined module orientation, shorter ﬁber length or lower packing density. It was also found that gas bubbling not only enhanced the permeation ﬂux by average 26% when concentrating feed solution from 18% salt concentration to saturation, but also delayed the occurrence of major ﬂux decline due to crystal deposition when compared to the module with spacers. These results were conﬁrmed by membrane surface autopsy at different operating stages using SEM.